Newtonian mechanics a modelling approach - Raine, Derek J. 1946- (Essentials of physics series, 2017)
Newtonian mechanics is taught as part of every physics program for several reasons. It is a towering intellectual achievement; it has diverse applications; and it provides a context for teaching modelling and problem solving. This text gives equal prominence to all three missions.